Translator's Voice in Discursive Creation Translation on The Mahen’s Pura-Pura Lupa Song - Mukminin, Muhamad Saiful (Journal of Language, Literature and Teaching, 2024)
This study aims to analyze the translator's voice in the discursive creative translation of the song Pura-Pura Lupa by Mahen. Using a qualitative descriptive approach, the research seeks to explore the translator's role in reconstructing meaning through linguistic adaptation and cultural reinterpretation. The primary data consists of the song lyrics in the source language (Indonesian), performed by Mahen, and their translation into the target language (English), performed by Emma Heesters. Data collection was conducted using a documentation method by gathering and comparing both versions of the lyrics. The theoretical foundation of this study is based on the theory of discursive creative translation, which emphasizes the translator's active role in shaping discourse. Following an interactive model, the analysis process consists of three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the translator's voice is reflected in structural and semantic changes, idiomatic adaptation, and shifts in perspective. This study reinforces the idea that translation is not merely a mechanical process but a discursive act that requires linguistic and cultural sensitivity.